tanhx = sinhx / coshx(min.value-1 & max.value1) cosh2x - sinh2x = 1
cothx = coshx / sinhx sech2x + tanh2x = 1
sechx = 1 / coshx coth2x - csch2x = 1
cschx = 1 / sinhx 1 - tanh2x = 1 / cosh2x
cothx = 1/ tanhx coth2x - 1 = 1 / sinh2x
sinh(-x) = - sinhx  
cosh(-x)= coshx  
tanh(-x) = -tanhx  
sin x = (eix - e-ix ) / 2i sin x = x - x3 / 3! +x5 / 5! -x7 / 7! +...........
sinhx = (ex - e-x ) / 2 sinhx = 1 + x3 / 3! + x5 / 5! + x7 / 7! +...........
cos x = (eix + e-ix ) / 2 cos x = 1 - x2 / 2! +x4 / 4! -x6 / 6! +...........
coshx = (ex + e-x ) / 2 coshx = 1 + x2 / 2! + x4 / 4! + x6 / 6! +...........(*)
sinhx = -i sinix (*) The equation of parabola can be written as y=1 + x2 / 2! So for small values of x, y=coshx is almost similar to a parabola.
coshx = cosix  

 

 x ≥ 0 sinhx = u coshx = u tanhx = u cothx = u sechx = u cschx = u
sinhx u √(u2-1) u / √(1-u2) 1 / √(u2-1) √(1-u2) / u 1 / u
coshx √(1+u2) u 1 / √(1-u2) u / √(u2-1) 1 / u √(1+u2) / u
tanhx u / √(1+u2) √(u2-1) / u u 1 / u √(1-u2) 1 / √(1+u2)
cothx √(1+u2) / u u / √(u2-1) 1 / u u 1 / √(1-u2) √(1+u2)
sechx 1 / √(1+u2) 1/u √(1-u2) √(u2-1) / u u u / √(1+u2)
cschx 1 / u 1 / √(u2-1) √(1-u2) / u √(u2-1) u / √(1-u2) u
x < 0 sinhx = -u coshx = u tanhx = -u cothx = -u sechx = u cschx = - u
sinhx - u √(u2-1) -u / √(1-u2) -1 / √(u2-1) √(1-u2) / u -1 / u
coshx √(1+u2) u 1 / √(1-u2) u / √(u2-1) 1 / u √(1+u2) / u
tanhx -u / √(1+u2) √(u2-1) / u -u -1 / u √(1-u2) -1 / √(1+u2)
cothx -√(1+u2) / u u / √(u2-1) -1 / u -u 1 / √(1-u2) -√(1+u2)
sechx 1 / √(1+u2) 1/u √(1-u2) √(u2-1) / u u u / √(1+u2)
cschx -1 / u 1 / √(u2-1) -√(1-u2) / u -√(u2-1) u / √(1-u2) -u